Distributed thermal-aware task scheduling for 3D network-on-chip - Cui, Yingnan (2013)
The development of 3D integration technology significantly improves the bandwidth of network-on-chip (NoC) system. However, the 3D technology-enabled high integration density also brings severe concerns of temperature increase, which may impair system reliability and degrade the performance. Task scheduling has been regarded as one effective approach in eliminating thermal hotspot without introducing hardware overhead. However, centralized thermal-aware task scheduling algorithms for 3D-NoC have been limited for incurring high computational complexity as the system scale increase. In this paper, we propose a distributed agent-based thermal-aware task scheduling algorithm for 3D-NoC which shows high scheduling efficiency and high scalability. Experimental results have shown that when compared to the centralized algorithms, our algorithm can achieve up to 13 °C reduction in peak temperature of the system without sacrificing performance.